Research on Dynamic and Thermal Effects Based on the Calculation of the Short-Circuit Current in Low-Voltage DC Distribution Systems for Civil Buildings - Wei, Qiang; Ni, Gaojun; Feng, Jianhua; Ma, Hao (Applied sciences, 2023)
The verification of short-circuit effects is very important for ensuring the safety of equipment and power systems. Compared with that in alternating current (AC) systems, research on this issue in direct current (DC) systems is scarce, and it is urgently necessary to develop an accurate verification method for applications in DC systems. This research establishes an equivalent model of a pole–pole cable short-circuit according to the characteristics of low-voltage DC distribution systems in civil buildings. Through theoretical analysis and numerical simulation, the development process of a short circuit is summarized, and the methods of verifying dynamic and thermal effects based on the time-domain characteristics of the short-circuit current are specified. By calculating the peak value and Joule integral of the short-circuit current, in comparison with those in the IEC 61660 (1997) standard, this research points out that the method in the IEC 61660 (1997) standard is insufficient. Finally, the short-circuit peak current is greatly affected by the DC-link capacitance, the steady-state current is directly related to the filter inductance of the AC-link; and the verification of the thermal effect requires the calculation of the Joule integral in the transient and steady state.